عبد الرحمن عزام ودوره في الحركة الوطنية الليبية 1916-1952م (Faculty of Education Scientific Journal, 2025)
This study seeks to clarify the role of Abdel Rahman Azzam in the Libyan issue. He is one of the most important Egyptian figures who has an important role in the Libyan resistance movement. He participated in resolving many tribal disputes and was one of the founders of the Tripolitan Republic. He became its advisor and was appointed a member of the government of the Tripolitan Republic. He was an advisor to the Central Reform Authority, and the Italians considered him one of the most prominent leaders who made Italian rights limited to the coastal areas. Upon his return to Egypt, he played a role in advocating the Libyan issue by writing in Egyptian newspapers, and upon assuming the secretariat of the Arab League, he cared more about the Libyan issue and made every effort to defend the Libyans and achieve the country’s unity and independence, and this is what we will explain in this study.
Keywords: National Movement; Arab Republic of Independence; World War II